Perancangan Media Evaluasi Mata Pelajaran Bahasa Inggris Kelas VII Mengunakan Wordwall di MTSN 4 Lima Puluh Kota - Hasanah Fitri; Sarwo Derta (KOLONI, 2024)
The learning evaluation media used in MTSN 4 Lima Puluh Kota is still simple, due to the lack of teacher understanding in making and using information technology-based learning evaluation media. Of course, this makes learning evaluation less effective and interesting. The purpose of this study is to design information technology-based evaluation media in the form of educational games using Wordwall in English subjects for class VII at MTSN 4 Lima Puluh Kota. The research method used is the Research and Development (R&D) method. Meanwhile, for the media development model, the researcher used the Hannafin and Peck model, which consists of 3 phases, namely (1) needs analysis, (2) design and (3) Develop and Implement, where the three phases are connected in evaluation and revision activities. The results of this study can be concluded that the designed media product is declared valid, practical and effective and can be used by teachers and students in the learning evaluation process, this can be seen from the results of the product test that the researcher conducted, from the validity test getting an average value of 0.86 with a valid category, then the practicality test obtained an average value of 0.85 with a high category and for the product effectiveness test getting an average value of 0.85 with a high effectiveness category.